Habituasi Subkultur Tionghoa di tengah Dominasi Melayu Bangka: Politik Berbagi Peran - Ibrahim Ibrahim; Arief Hidayat; Herza Herza (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2022)
Ethnic Chinese is an ethnic group that has long been part of the people of Bangka Island. The harmonious relationship between the ethnic Chinese and the indigenous population shows that the habituation process is going well so that their existence is accepted as a social reality. This study uses descriptive qualitative methods to collect data from interviews and observations in regencies/municipalities within Bangka Island. This research finds that the existence of the Chinese ethnicity has been processed by strengthening the four main capitals of the Chinese ethnicity (Bourdieu’s view): economic capital, social capital, cultural capital, and symbolic capital. Capital control has encouraged good role-sharing politics because capital control is carried out transformatively. It is not surprising that the Chinese minority subculture, although in many ways it feels dominant, can still be accepted as a social reality that forms intercultural harmony on Bangka island.